Sacred History: Uses of the Christian Past in the Renaissance World. Edited by Katherine Van Liere, Simon Ditchfield, and Howard Louthan - Apetrei, Sarah (The journal of theological studies, 2013)
Ecclesiastical history, according to the Oratorian Cesare Becilli, writing in the 1630s, ‘always accompanies sacred doctrine, not as a waiting-woman but as an ally and indeed perhaps an elder sister’. This wonderful, meticulously researched collection of essays tracks the changes but also the continuities in the role of ‘sacred history’ in an age typically characterized as one of intellectual and religious transformation. It is a story of paradoxes. Critical scholarship and new philological methods bolster confessional apologetics alongside ‘questionable scholarly practices’ (p.